Rasa, Harga, Higiene dan Kebersihan Berkaitan dengan Pemilihan Tempat Makan Sari Laut - Jumakil Jumakil; Virda Yanti; Harleli Harleli; Fithria Fithria (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Background: Sari Laut food stalls are one of the food stalls that thrive in Kendari City and is also widely visited by the people of Kendari City and are one of the dining options. Objective: The purpose of this study is to determine what factors influence the selection of Sari Laut in Kendari City. Methods: This type of research is quantitative with a cross-sectional study design. This research was conducted in Mandonga Subdistrict, Poasia Subdistrict, Baruga Subdistrict, Kambu Subdistrict, Kadia Subdistrict, and West Kendari Subdistrict. The population of this research is 56 Sari Laut. The sample is 112 respondents of buyers at Sari Laut. Results: there was a significant relationship between the taste of food (ρValue = 0.004) and the price of food (ρValue = 0.023) with the selection of a place to eat seafood. There is no significant relationship between personal hygiene (ρValue = 0.091), cleanliness of eating places (ρValue = 0.402), and cleanliness of cutlery and cooking utensils (ρValue = 1,000) with the selection of a place to eat seafood. Conclusion: factors related to the choice of Sari Laut stalls, namely the taste of food and the price of food.